Estudios genéticos en linfomas cutáneos de células T - Huamán Garaicoa, Fuad Olmedo (2016)
Mycosis fungoides (MF) is a clonally derived lymphoproliferative disorder that\npreferentially involves the skin, which etiology and pathogenesis remains elusive.\nMorphological and clinical features are not always accurate enough to predict the disease\noutcome. Comparative genomic hybridization and microarrays have shown imbalances of\nCDKN2A (9p21) and C-MYC (8q24), with probable prognostic value in this pathology. In\naddition, miR-155 overexpression was observed in several hematological and solid tumors,\npromoting genomic instability, proliferation, and survival of malignant cells. In this study,\nwe have evaluated CDKN2A losses and C-MYC gains and their association with miR-155\nexpression, in patients with diagnosis of MF. Results were correlated with\nclinicopathological features of patients. The study was performed on formalin-fixed and\nparaffin-embedded biopsies from 36 patients with MF (26 males; median age 62.5 years,\nrange: 31-82 years): 16 cases were tumor stage MF (T-MF), 13 were MF with histological\ntransformation to a large T-cell lymphoma (TR-MF) and 7 were folliculotropic MF (F-MF)\nvariant. FISH analysis using OTS9P21.3 (CDKN2A) and OTS8Q24 (C-MYC) probes\n(LiVE-Lexel, Argentina), was performed. Gene expression was quantified by real time\nPCR using TaqMan methodology. Ten control samples from benign skin diseases were also\nevaluated. The study was approved by the local Ethics Committee. All individuals provided\ntheir informed written consent. FISH study was performed in 34 patients, 20 (59%) showed\ngenomic alterations (GA): 8 (40%) cases had CDKN2A deletion, 7 (35%) showed C-MYC\ngains and 5 (25%) exhibited both anomalies. CDKN2A deletion was observed in 7/13\n(54%) TR-MF, 4/7 (57%) F-MF and 2/16 (12.5%) T-MF (p=0.03); meanwhile C-MYC gain\nwas detected in 7/13 (54%) TR-MF and 5/7 (71.4%) F-MF. Thus, GA rate was lower in TMF\n14.3% with respect to TR-MF 92.3% and F-MF 85.7% (p=0.001 and p=0.004,\nrespectively). These aberrations were more frequent in head, neck and lower limbs (77.8%)\nin contrast with trunk and upper limbs (40%) (p=0.03). By immunohistochemistry, majority\nof cases with <25% CD30+ cells did not show GA (91% vs 9%) (p=0.01); meanwhile\npatients of GA group had more high median proliferation index (Ki-67) (49.5%) in\ncomparison to cases with no genomic aberrations (NA) (5%) (p=0.003). Interestingly, TRMF\nwith follicular origin had more frequently 9p21 deletion (80%) and less 8q24 gain\n(40%) respect to classic origin (42.8% and 71.4%, respectively). Clinical response to treatment was absent in 11/20 (55%) of cases with GA vs. 2/14 (14.3%) patients with NA\n(p=0.02). Although no significant differences were reached, mean LDH and Beta 2\nmicroglobulin levels and extracutaneous relapse were higher with respect to those with NA.\nIn addition, the group with GA showed shorter overall survival (92 months) compared to\ncases with NA, that not reached the median survival (Log-rank p=0.04), indicating their\nassociation with poor outcome. Gene expression analysis (n=36) showed miR-155\nupregulation in 25% TR-MF and 28.6% F-MF and in only 7.7% T-MF. No miR-155\nexpression was observed in controls. The correlation with FISH results found miR-155\noverexpression in 26.3% of patients with GA and 8.3% of cases with NA. Our results\nshowed high proportion of 9p21 losses and 8q24 gains in MF patients. TR-MF exhibited\nthe highest frequency of GA, supporting a role in the process of neoplastic transformation.\nAlthough the number of F-MF is reduced in our series, this morphological variant would\nseem to be associated to an increased frequency of genomic imbalances. Moreover, our\nfindings on miR-155 expression support its relation with genomic instability and tumor\ndevelopment, contributing a better biological characterization of this pathology.